The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2217/imt.15.64
|View full text |Cite
|
Sign up to set email alerts
|

Alphavirus-Based Vaccines in Melanoma: Rationale and Potential Improvements in Immunotherapeutic Combinations

Abstract: Immune checkpoint blockade has formally demonstrated the clinical benefit of immunotherapy against melanoma. New immunotherapeutic modalities are currently explored to improve the management of relapsing/refractory patients. Potent antitumor vaccines would have the advantage to promote long-lasting tumor control while limiting autoimmunity. Alphavirus vectors and nonreplicating particles offer versatile platforms to deliver antigen expression and immunize against cancer. They have shown promising preclinical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 129 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…B16F10 melanoma cells were implanted intradermally (10 5 cells, for tumor-growth and survival analyses) or subcutaneously in matrigel (Matrigel Matrix Growth Factor Reduced, Becton Dickinson) (2×10 5 cells, for immune-cell infiltrate analyses). Vaccination with VRP-TRP2 (AlphaVax Inc.) was performed by injection of 1×10 6 virus-like replicon particles (VRPs)(Zappasodi and Merghoub, 2015) expressing mouse TRP2 into the plantar surface of each footpad for 3 times 1 week apart, starting 3 days after tumor implantation(Avogadri et al, 2014). Treatment with αCTLA-4 (clone 9D9, BioXcell, 100 μg or 300 μg/injection), αPD-1 (clone RMP1-14, BioXcell, 250 μg/injection) or the matched isotype IgGs (BioXcell) was started 3–4 (optimal treatment) or 6–7 days (suboptimal treatment) after tumor implantation for respectively 5 or 4 intraperitoneal (i.p.)…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…B16F10 melanoma cells were implanted intradermally (10 5 cells, for tumor-growth and survival analyses) or subcutaneously in matrigel (Matrigel Matrix Growth Factor Reduced, Becton Dickinson) (2×10 5 cells, for immune-cell infiltrate analyses). Vaccination with VRP-TRP2 (AlphaVax Inc.) was performed by injection of 1×10 6 virus-like replicon particles (VRPs)(Zappasodi and Merghoub, 2015) expressing mouse TRP2 into the plantar surface of each footpad for 3 times 1 week apart, starting 3 days after tumor implantation(Avogadri et al, 2014). Treatment with αCTLA-4 (clone 9D9, BioXcell, 100 μg or 300 μg/injection), αPD-1 (clone RMP1-14, BioXcell, 250 μg/injection) or the matched isotype IgGs (BioXcell) was started 3–4 (optimal treatment) or 6–7 days (suboptimal treatment) after tumor implantation for respectively 5 or 4 intraperitoneal (i.p.)…”
Section: Star Methodsmentioning
confidence: 99%
“…To better understand the mechanisms underlying CTLA-4 and PD-1 blockade, here we investigate modulation of CD4 + Foxp3 − PD-1 hi T cells (4PD1 hi ) during these treatments. We previously reported that lack of intra-tumor 4PD1 hi accumulation was associated with improved therapeutic activity of an alphavirus-based anti-melanoma vaccine (VRP-TRP2) in combination with immunomodulatory Abs in B16-bearing mice(Avogadri et al, 2014; Zappasodi and Merghoub, 2015). CTLA-4 blockade, which produced the greatest increases in intra-tumor 4PD1 hi , was the least efficient modality to enhance VRP-TRP2 activity(Avogadri et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of therapeutic TAAs expressed by alphaviruses were previously summarized [124,126,131]. An SFV vector encoding the P1A testis antigen, expressed on mast cell tumors, was shown to be effective at treating murine mastocytomas [124,126].…”
Section: Tumor-associated Antigensmentioning
confidence: 99%
“…Human epidermal growth factor (HER2)/neu proto-oncogene (neu) was expressed by a VEE-VRP to treat murine breast cancers [124,126,131]. VRP-neu vaccination pre-vented tumor formation and induced high levels of neu-specific CD8 T cells and anti-neu antibody [135].…”
Section: Tumor-associated Antigensmentioning
confidence: 99%
“…Melanoma is a cancer indication that has received plenty of attention, including prophylactic and therapeutic applications of alphaviruses ( Zappasodi and Merghoub, 2015 ). In this context, VEE particles expressing the tyrosine-related protein-2 (TRP-2) showed humoral immune responses, anti-tumor activity and prolonged survival in a B16 mouse melanoma model ( Avogadri et al, 2010 ).…”
Section: Alphavirus Vectors In Tissue-specific Cancer Therapymentioning
confidence: 99%